KEBIJAKAN PENATAAN DAN PEMBENTUKAN ORGANISASI PERANGKAT DAERAH (STUDI KASUS DI KABUPATEN CIANJUR PROVINSI JAWA BARAT) - Fernandes Simangunsong (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
This research is a form of study possibilities to assess and formulate mechanisms structuring and establishment of regional organizations in Indonesia, which in this study tested on Regency Cianjur of West Java province , after the enactment of Law No. 23 Year 2014 on Regional Government 's new , where the presence of Act No. 23 of 2014 , the Law No. 32 of 2004 as well as all technical rules under it should be changed and adjust the product of public policy which includes the new government regulations governing penatan organization ie government Regulation No. 41 of 2007 on penatan organization. Government regulations that the old should be replaced and re-adjusted to the conditions and potentials which exist in hopes that the upcoming organizational structuring can improve and enhance institutional performance effectively and efficiently . Currently the draft government regulation in lieu of government regulation No. 41 of 2007 was the pilot phase and the duty of academics to help the public testing phase and one of them tested in Cianjur. With this assessment is expected to provide recommendations to the fore in determining policy on the restructuring and the establishment of regional organizations in Cianjur after the enactment of Law No. 23 Year 2014 on Regional Government and the latest government regulations on organizational management. This study used a sample saturated in the sample area where this research takes all the data elements both primary and sekuder in the region or working unit (SKPD ) in Cianjur , nice element Secretariat staff area and the Parliament Secretariat, Elements Line Office , Elements auxilary Agency and offices , other suPeraturan Pemerintah (PP)orting elements Civil Service Police Unit and the Inspectorate as well as the line element for Regional and Sub -districts , to test the strength and potential in each SKPD using measurement instruments of the latest draft regulations. Keywords : Local government , Product Public Policy , Organizational Structuring